(untitled) (Architecture Image Studies, 2025)
The phenomenon of child exploitation as beggars and vagrants is a serious problem that threatens the safety and development of children and requires the attention of parents, families, communities, the government, and law enforcement officials. Handling child exploitation through a legal (repressive) approach that only relies on the police and civil service police has not been effective and optimal in preventing the increasingly worrying practice of child exploitation. This study aims to explore and find a concept for handling child exploitation as beggars and vagrants through a community-based approach, as well as to formulate and implement a concept for handling child exploitation as beggars and vagrants based on a community approach. Methodology: This type of research is empirical research, using a legal sociology approach, a legal anthropology approach, and a legal psychology approach. The data collection technique is carried out using a qualitative approach with a case study. The results of the study indicate that the exploitation of children as beggars and vagrants in Bima City is caused by a lack of parental/family supervision, poverty, dropping out of school, minimal child activity in positive activities, incomplete regulations and policies, and the community is still permissive towards begging and vagrancy activities. Furthermore, the concept of overcoming the exploitation of children as beggars and vagrants must use a community-based approach that emphasizes the active role of the community. The implementation of this concept is carried out through child protection and monitoring programs, holding rehabilitation and reintegration programs for children who are victims of exploitation, and creating a child-friendly village/sub-district environment that is physically and socially safe, comfortable, and supports optimal child growth. The research purpose is to give an analysis on the criminal policy concept for handling child exploitation as beggars and vagrants through a community-based approach. The scientific contribution from this research is that it offers a concept for handling child exploitation as beggars and vagrants based on a community approach.